2018
DOI: 10.1098/rsos.181121
|View full text |Cite
|
Sign up to set email alerts
|

Failure modes analysis of electrofluidic display under thermal ageing

Abstract: Dielectric failure as well as optical switching failure in electrofluidic display (EFD) are still a bottleneck for sufficient device lifetime. In this study, a dielectric redundancy-designed multilayer insulator of ParyleneC/AF1600X was applied in an EFD device. The reliability performance was systematically studied by tracking the applied voltage-dependent leakage current and capacitance changes (I–V and C–V curves) with thermal ageing time. The multilayer insulator shows a more stable performance in leakage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, the charge trapping phenomenon can cause an asymmetric electrowetting effect [11], contact angle saturation, and oil backflow [12]. These problems not only directly lead to dielectric failure [13], but also make a challenge for the stable display and precise control of grayscales. The strength of the charge trapping effect is related to the polarity of the driving voltage, type, and pH value of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the charge trapping phenomenon can cause an asymmetric electrowetting effect [11], contact angle saturation, and oil backflow [12]. These problems not only directly lead to dielectric failure [13], but also make a challenge for the stable display and precise control of grayscales. The strength of the charge trapping effect is related to the polarity of the driving voltage, type, and pH value of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…By constructing an organic-polymer and AF multilayer structure, the reliability of EWD can be enhanced. For example, our research showed that the double-layer structure of parylene C and AF 1600 could be used to prevent dielectric breakdown, and the stability of EWD can be improved [19] . The epoxy resin, which is the main component of photoresist has a dielectric constant ε around 3 to 4, and it has good filmforming properties.…”
Section: The Dielectric Layer and Liquid Materialsmentioning
confidence: 94%
“…Dong et al [ 18 ] fabricated a Parylene C and AF 1600 double layer structure to prevent dielectric breakdown. The advantages of a double layered dielectric material in terms of stability and reliability over a single layer dielectric material were evaluated by measuring the leaking electric charge.…”
Section: Materials: Multilayer Dielectricmentioning
confidence: 99%
“…The corresponding microscopy picture of the damage is given. (Images are reproduced from reference [ 18 ] with the permission of the Royal Society).…”
Section: Figurementioning
confidence: 99%